Gurunya Manusia Menjadikan Semua Anak Istimewa Semua Anak Juara - Diani Syahfitri; Dian Anggeraini; Emha Fidiyan Akhadi (peduli riset dan pengabdian masyarakat, 2022)
Education becomes a place to shape a person's quality through the learning process carried out at school. Low learning outcomes are a problem that is often faced by educators in the learning process. One of the factors causing this to happen is the lack of understanding and use of appropriate learning styles for students, this is also a problem in learning at MIS Miftahul Ula, Pematang Cengal Timur Village. For this reason, a socialization activity regarding children's learning styles and the application of home care services for students was carried out to educators at MIS Miftahul Ula. The purpose of this service is so that educators can facilitate learning in the classroom according to the learning styles preferred by students. The method used in this service activity is the provision of training and materials with lecture, discussion and question and answer methods. The results obtained after the activity was carried out were the participants' understanding of learning styles and the application of home care became better and could apply them to the learning process in the classroom.